Covid Terror and Government Appeals to Public Interest for Eid in the Village - Hassan, Daniels; Vera, Awada; Visconte, Arda (Journal Markcount Finance, 2023)
This research discusses the Covid Terror and the Government's Appeal to Public Animo for Eid Al-Fitr in Villages in 2019-2022. The aim of the study was to find out the interest of the vegetable traders in the village during the Covid-19 outbreak and the Government's appeal to ban crowds and easing it. The research design uses descriptive and associative quantitative methods with observative media, interviews and questionnaires. Questionnaire data sample respondents are summarized, analyzed and tested for validity and reliability. Then tested with statistical tools to obtain the weighted quantity of each variable. The results of the Multiple Linear Regression test, a constant value of 42.969 means that the condition when the variable Y (Animo Going Home for Eid) has not been influenced by the independent variables X1 (Spread of Covid-19) and X2 (Government Circular). The b1X1 value in the equation is 0.91, meaning that the variable X1 (Spread of Covid-19) has a positive effect on the Y variable (Animo Going Home with Eid) has an effect of 0.91 on Variable Y (Animo going home with Eid) meaning that other variables are not included in this study. The b2X2 value of 0.77 means that the X2 variable (Government Circular Letter) has a positive influence on the Y variable (Animo Going Home for Eid), which has an effect of 0.77 on variable Y (Animo for Homecoming with Eid), meaning that other variables are not investigated. The X1 Correlation value (Covid-19 Spread) is 0.182 and the Correlation value of the X2 variable (Government Circular Letter) is 0.189. Thus it can be concluded that there is a very low and one-way correlation level because the two variables have a correlation value between 0.000-0.199 which means that the relationship level is also very low. Coefficient of Determination Test (R2) The coefficient of determination (R Square) is 0.44 or 44 percent, proving that variable Y can only be explained by variables X1 and X2 by 44 percent, and the remaining 56 percent is explained by other variables not examined in the study This.